Titik Temu Tujuan Pendidikan Islam dan Indonesia - Samsirin Samsirin; Siti Hardiyanti (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
One of the most important aspects in a nation is the aspect of education that had been applied. The progress of a nation's resignation is largely determined by the advance of education in that country. Therefore, education must be managed properly to achieve the goal of education that have been aspired. As a country with a predominantly Muslim population, Indonesia should pay special attention to the Islamic educational system as the needs of its community. The purpose of this paper is to discuss about the purpose of education in Indonesia in the perspective of Islam. This paper is written using the literature review method by analyzing a problem based on the relevant literature. After examining several things, such as educational objectives in general, the purpose of education in Islam and the objectives of Islamic education in Indonesia, then obtained the formulation of Islamic education objectives in Indonesia. The research analysis shows that the purpose of education in Indonesia in the Islamic perspective can be seen from several aspects, namely first, making the element of Tawheed as the main goal. Second, make noble character as the fruit of faith and taqwa to God Almighty. And thirdly, it has an element of balance between the purpose of life in the world and in the Hereafter and not only attaches importance to one element.